Neutrino-pair interactions in astrophysical systems - Colombi, Maria Paula (2020)
We study the effects produced by interactions among neutrinos upon extra-galactic neutrino-fluxes. We have assumed a separable type of pair interactions and performed a transformation to a quasi-particle mean field followed by a Tamm-Damcoff diagonalization. In doing so, we have adopted techniques originated in the quantum many-body problem, and adapted them to this specific case. The solutions of the associated eigenvalue problem provide us with energies and amplitudes which are then used to construct the neutrino response functions at finite density and temperature. The formalism is applied to the description of neutrinos produced in a SN environment.